2013
DOI: 10.1007/s10120-013-0233-2
|View full text |Cite
|
Sign up to set email alerts
|

Early gastric cancer: diagnosis, staging, and clinical impact. Evaluation of 530 patients. New elements for an updated definition and classification

Abstract: Background The prevention and early diagnosis of gastric cancer permit clinicians to discover the tumor in the initial phase, during which time it can be completely eradicated, endoscopically or surgically. Since Murakami gave the definition of early gastric cancer (EGC) in 1971, many authors have identified various subtypes of EGC with different morphological characteristics and clinical behaviour. Methods We evaluated retrospectively 530 patients: the median follow-up time was 10.4 months (range 0.3-29.2). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…However, further studies will be necessary scopic techniques and better knowledge of the problem have led to significant increase in EGC over the past few years [18]. According to different screening programs in Japan and Korea about fifty percent of treated patients had an early tumor stage [6,18]. The prevalence of EGC in Western countries is not really known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further studies will be necessary scopic techniques and better knowledge of the problem have led to significant increase in EGC over the past few years [18]. According to different screening programs in Japan and Korea about fifty percent of treated patients had an early tumor stage [6,18]. The prevalence of EGC in Western countries is not really known.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the most appropriate prevalence of the papillary subtype of EGC in the pathological diagnosis of GC will be important in future [3]. However, further studies will be necessary scopic techniques and better knowledge of the problem have led to significant increase in EGC over the past few years [18]. According to different screening programs in Japan and Korea about fifty percent of treated patients had an early tumor stage [6,18].…”
Section: Discussionmentioning
confidence: 99%
“…It might be easily thought out that tumor-related factors such as tumor size, lymphatic invasion, and venous invasion could be an indicator for progressive potential of malignant tumors [1–3]. However, except for stage of the tumor, there have not been any criteria using histopathological tumor-related factors to determine the outcome of the patients with gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…As other authors found grading, lymph vessel invasion and tumor size as prognostic in early tumor stages mainly with lymph node involvement [10–14], employing a more detailed analysis (N0 versus N+) of the tumor, might explain these differences.…”
Section: Discussionmentioning
confidence: 86%
“…In the search for additional and refined prognostic risk factors in advanced tumor stages, several studies analyzed histomorphological criteria like tumor size, lymphatic vessel invasion, vein invasion, grading, Lauren classification, WHO classification, and MING classification [9–14]. Several studies described molecular markers considered predictive for survival of which we selected for immunohistochemical evaluation and categorized in subgroups: markers for proliferation (Ki-67 [15]), cell cycle regulation (Cyclin E [16–18], p21 [19], TP53 [20]), apoptosis (BAX [21], BCL [22], Survivin [23–25]), cell adhesion (E-cadherin [26–28]), cell differentiation (CDX2) [29], SHH (Sonic hedgehog) [30], TROP2 [31], HIF1A (hypoxia induced factor 1α) [32] and mismatch repair deficiency [33].…”
Section: Introductionmentioning
confidence: 99%